Confronting Misinformation: TikTok Community Response to Fake Hadith in #8junimuhammadwafat and Verification Efforts on Social Media - Mika, Almughni; Fauziyah, Farichatul (Universitas Islam Internasional Darullughah Wadda'wah, 2025)
The spread of false information, including hadiths, has become increasingly rampant in the digital era, especially on social media platforms like TikTok. This can mislead the understanding of Muslims and affect their beliefs. This study aims to examine the TikTok community's response to the dissemination of false hadiths through the hashtag #8junimuhammadwafat, as well as the verification and education efforts undertaken by users. Using a netnographic approach, data were collected through content observation related to the hashtag, including user interactions such as likes, comments, and content sharing. The results indicate that TikTok users' responses vary, ranging from criticism of the authenticity of hadiths to fact-based educational efforts by several accounts actively verifying information. This study emphasizes the importance of digital literacy in managing religious information on social media and provides insights into the dynamics of information among TikTok users. It is hoped that this research will help raise awareness of the importance of information verification in a religious context.